2016
DOI: 10.1007/s11554-016-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient parallelization on GPU of an image smoothing method based on a variational model

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag Berlin Heidelberg. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In 2016, Gulo, et al presented and discussed implementation of a highly efficient algorithm for image noise smoothing based on general purpose computing on GPU techniques. They suggested that the use of GPU techniques facilitate quick and efficient smoothing of images even when performed on large dimensional data sets [Gulo et al, (2016)]. In 2017, Bahri, et al introduced an algorithm to optimize the computing time of feature extraction methods for colour images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Gulo, et al presented and discussed implementation of a highly efficient algorithm for image noise smoothing based on general purpose computing on GPU techniques. They suggested that the use of GPU techniques facilitate quick and efficient smoothing of images even when performed on large dimensional data sets [Gulo et al, (2016)]. In 2017, Bahri, et al introduced an algorithm to optimize the computing time of feature extraction methods for colour images.…”
Section: Related Workmentioning
confidence: 99%
“…It allows C programmers to write parallel codes for GPU using a few easy to use language extensions. The number of CUDA cores available for processing depends upon the graphic card's CUDA architecture [CUDA C programming Guide, (2019)], [Chakrabarti et al,(2012)], [Che et al, (2008)], [Nickolls et al, (2016) CUDA architecture is suitable for image processing applications (Zhiyi et al, 2008), (Y. K. Wang & Huang, 2014), (Kang et al, 2014), (Ferreiro et al, 2013), (J. , (Gulo et al, 2016). In this paper, to address the time complexity of NLM algorithm, a model for parallelization of NLM algorithm using CUDA is proposed.…”
mentioning
confidence: 99%
“…Noise reduction has been performed with different methods on different images . To determine the most appropriate algorithm for noise reduction (ie, to avoid poor de‐noising), the type of noise in the image should be identified.…”
Section: Antibody Validation By Image Analysismentioning
confidence: 99%
“…Noise reduction has been performed with different methods on different images. [16][17][18] To determine the most appropriate algorithm for noise reduction (ie, to avoid poor de-noising), the type of noise in the image should be identified. Therefore, we chose 3 regions (at least 100 × 100 pixels), which have homogenous (or close to homogenous) intensity values, from images and analyzed their histograms to identify noise type.…”
Section: Noise Modeling and Reductionmentioning
confidence: 99%
“…Gulo et al [34] described in their study how to use the high-performance computing CUDA-based architecture as a computational infrastructure to accelerate an algorithm for noise image removal. The parallel GPU-based implementation developed was compared against the corresponding sequential CPU-based implementation in several experiments.…”
Section: Image Filteringmentioning
confidence: 99%